Salivary microbiota dysbiosis and elevated polyamine levels contribute to the severity of periodontal disease - Md Haroon Rashid; Sandhya Pavan Kumar; Resma Rajan; Anitha Mamillapalli (BMC Oral Health)
Abstract Background The oral cavity is a complex environment which harbours the second largest and most diverse microflora after the gastrointestinal tract. The bacteriome in the oral cavity plays a pivotal role in promoting the health and well-being of human beings. Gingivitis, an inflammation of the gingival tissue, arises due to plaque accumulation on the teeth, often leads to periodontitis. Progression of periodontitis resulting in clinical attachment loss, bone loss and eventually the tooth loss is poorly understood. The present study explores the transitions in microbioata, oxidative stress and polyamine levels during the disease evolution which can contribute to developing effective therapeutic approaches. Methods Saliva samples were collected from seventy-two individuals after procuring informed consent who were either healthy, gingivitis or stage-specific periodontitis patients. Periodontitis stage was confirmed by clinical and radiographic analysis. Microbiota analysis was carried out by 16S rRNA sequencing on the Nanopore PromethIONsystem platform of Oxford Nanopore technologies. Polyamine levels were quantified with fluorescence spectrophotometer. Ornithine decarboxylase quantification was evaluated by ELISA method. Antioxidant levels of the salivary samples were measured by DPPH, SOD, and catalase assays. Autophagy was measured by acid phosphatase assay. Result The salivary microbiota exhibited significant changes in their abundance and diversity between healthy individuals and those with conditions such as gingivitis, and chronic periodontitis. A significant increase in polyamines and ornithine decarboxylase was found in gingivitis and various stages of periodontitis. Elevated oxidative stress observed in gingivitis and periodontitis could have resulted in cell death. Conclusion The current study shows the role of salivary microbiota and polyamines in gingivitis and different periodontitis stages. The progressive elevation of Streptococcus levels from gingivitis to periodontitis, coupled with polyamine concentrations, may serve as a promising identification marker for assessing the severity of periodontal disease. Insight into the oral bacterial flora and associated physiological changes provide a foundation for targeted therapeutic interventions in gingivitis and periodontitis diseases emphasising the importance of personalised oral health management strategies.